Exploring Infection in Primary Total Ankle Arthroplasty - Albert T. Anastasio MD; Kevin Wu BS; Conor N. O'Neill MD; Emily Joan Luo BS; Billy I. Kim MD; James A. Nunley MD; James K. DeOrio MD; Mark E. Easley MD; Samuel B. Adams MD (Foot & Ankle Orthopaedics)
Category: Ankle; Ankle Arthritis Introduction/Purpose: Infection is a serious complication of primary total ankle arthroplasty (TAA) and can lead to implant failure and revision surgery. While various patient demographics, comorbidities, and surgical factors have been associated with an increased risk of infection, evidence is limited, and further research is required to better understand infection in TAA. This study aims to analyze risk factors of infection and explore outcomes following infected TAA. Methods: A retrospective cohort study was conducted using data from a single institution from 2002 to 2022. Patients who underwent primary TAA and had subsequent infection were identified and matched using propensity-score matching (PSM) based on various demographic, comorbidity, and surgical factors. Demographics were compared between the matched groups using Mann-Whitney U test and Fisher's exact test. The outcomes following infection were identified and summarized using descriptive statistics. Results: A total of 1,863 patients who underwent primary TAA were identified, and 19 (1%) were diagnosed with an infection. After PSM, there were no significant differences in age, gender, BMI, and smoking status between the cohorts. There was a statistically significant increase in the rate of diabetes in the infected cohort (26.3 vs. 15.3; p =0.01). Subsequent surgical intervention resulted in limb salvage in 18 (94.7%) cases. Two-stage revision to total ankle replacement was performed in 7 cases (36.8%), while revision to arthrodesis and isolated polyethylene exchange were each carried out in 4 cases (21.1%). One patient had to undergo amputation, however, at the time of the most recent follow-up (5.3%). All patients were found to be free of infection. Conclusion: This study demonstrated significantly increased rates of smoking and diabetes in the infected TAA cohort. Two-stage revision to TAR and revision to arthrodesis with isolated polyethylene exchange were successful in eradicating infection. Overall, a high rate of limb salvage was reported.